2007
DOI: 10.1128/mcb.02087-06
|View full text |Cite
|
Sign up to set email alerts
|

Mice with a Disruption of the Imprinted Grb10 Gene Exhibit Altered Body Composition, Glucose Homeostasis, and Insulin Signaling during Postnatal Life

Abstract: The Grb10 adapter protein is capable of interacting with a variety of receptor tyrosine kinases, including, notably, the insulin receptor. Biochemical and cell culture experiments have indicated that Grb10 might act as an inhibitor of insulin signaling. We have used mice with a disruption of the Grb10 gene (Grb10⌬2-4 mice) to assess whether Grb10 might influence insulin signaling and glucose homeostasis in vivo. Adult Grb10⌬2-4 mice were found to have improved whole-body glucose tolerance and insulin sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
154
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(170 citation statements)
references
References 61 publications
12
154
1
3
Order By: Relevance
“…Previous studies showed that Nrip1 plays an important role in controlling lipid and glucose metabolism (ROSELL et al, 2010). In agreement, a study using knockout mice with a disruption of the Grb10 gene was found to improve insulin sensitivity and to reduce adiposity (SMITH et al, 2007). An association of Nrip1 and Grb10 has not been described yet.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies showed that Nrip1 plays an important role in controlling lipid and glucose metabolism (ROSELL et al, 2010). In agreement, a study using knockout mice with a disruption of the Grb10 gene was found to improve insulin sensitivity and to reduce adiposity (SMITH et al, 2007). An association of Nrip1 and Grb10 has not been described yet.…”
Section: Discussionsupporting
confidence: 62%
“…GRB10 has been found to protect the vascular endothelial growth factor receptor from ubiquitin-mediated degradation in HEK293 cells [45]. Although GRB10 has been identified as a negative regulator of the insulin receptor [10], IRS1 levels are markedly reduced in skeletal muscle from mice with a targeted disruption of either GRB10 alone, or combined with the related GRB14 protein [46,47]. Intriguingly, in muscle from the Grb10-knockout mouse, insulin-induced tyrosine phosphorylation of IRS1 was increased, whereas insulin-induced phosphorylation of AktSer473 was decreased [46].…”
Section: Discussionmentioning
confidence: 99%
“…Although GRB10 has been identified as a negative regulator of the insulin receptor [10], IRS1 levels are markedly reduced in skeletal muscle from mice with a targeted disruption of either GRB10 alone, or combined with the related GRB14 protein [46,47]. Intriguingly, in muscle from the Grb10-knockout mouse, insulin-induced tyrosine phosphorylation of IRS1 was increased, whereas insulin-induced phosphorylation of AktSer473 was decreased [46]. In muscle from the combined Grb10/Grb14-knockout mouse, marked decreases were observed in insulin-stimulated IRS1 phosphorylation [47].…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic overgrowth also reflects the important role of Grb10 in placental development, with Grb10 deficiency resulting in increased placental size and efficiency (42). Postnatal overgrowth has been partially attributed to the increased lean mass observed in Grb10 deletion mice (37,38,43). Grb10 deletion mice have an increased number of muscle fibers and the molecular hallmarks of increased insulin signaling in muscle (44).…”
Section: Grb10 Is a Negative Regulator Of Growthmentioning
confidence: 99%
“…Notably, Grb10 overexpression is linked to severe pancreatic dysfunction and dysmorphia in juvenile mice (36). Reduction in Grb10 expression is associated with widespread neonatal and postnatal overgrowth, along with increased sensitivity to insulin (6,34,37,38). Pancreas-specific Grb10 deletion results in increased insulin production and improved glucose tolerance (39).…”
Section: Grb10 Is a Negative Regulator Of Growthmentioning
confidence: 99%